Traditions and future directions in research and education at the Pedagogical Institute of Saratov State University - Firsova, Tatyana G.; Gorina, Ekaterina N.; Bocharova, Elena E. (Известия Саратовского университета. Новая серия: Акмеология образования. Психология развития)
The relevance of the research is due to the need to analyze, conceptualize, and integrate both traditions and innovations in the research and education at the Teacher Training College of Saratov State University (SSU). Key focus areas include transformation of scientifi c schools, changes in classroom and extracurricular work, quantitative and qualitative transformation of practical training, formation of a common educational environment, and fostering interdepartmental interaction. The study aims to identify directions and strategies for developing research and education at the Teacher Training College of SSU. Methods (tools) include retrospective and comparative analyses of relevant scientifi c literature and bibliographic sources. Results highlight the strategies for research and education at the Teacher Training College of SSU, drawing on the analysis of methodological research of the founders of pedagogical, psychological, defectological, and methodical schools, as well as their substantive and technological content in response to modern challenges of higher pedagogical education. A scientifi c and educational cluster of the college has been established, identifying infrastructure and relevant scientifi c and methodological interests among the faculty. Conclusion: This research summarizes the transformation experiences of teacher training at Saratov State University, revealing strategies and future directions aligned with public demand and the current socio-cultural context. It presents common educational, personal development and research agendas of the Teacher Training College of SSU, focusing on integrating deep subject knowledge and innovative teaching methods, practice-oriented classes and extracurricular events. The study emphasizes close collaboration and interaction with educational organizations to cultivate traditional values, professional and personal qualities, and proactive behavior essential for future educators’ professional training. Practical significance: This study offers a model for replicating successful practices from the Saratov School of Higher Pedagogical Education.